The golden spoon : a novel - Maxwell, Jessa (Atria Books, 2023)
"When production for the tenth season of the hit cooking competition Bake Week begins at the gothic estate of the show's host and founder, celebrity chef Betsy Martin, everything seems normal. The six contestants are eager to prove their culinary talents over the course of five days, while Betsy struggles for control of the show with her new co-host, the brash and unpredictable Archie Morris. But as the baking competition gets under way, things begin to go awry. At first it's merely sabotage-sugar replaced with salt, a burner turned to high-but then someone shows up dead and suddenly everyone's a suspect"--